Designing technology tools to support engagement in mindfulness-based interventions: an analysis of teacher and student experiences. (August 2019) - Parsons, Christine E.; Jensen, Kasper L.; Roepstorff, Andreas; Fjorback, Lone O.; Linehan, Conor
Standard mindfulness-based interventions have significant at-home assignments of formal mindfulness practice as a key component. Engagement with formal home practice has been correlated with treatment outcomes, but participants often complete less than the assigned amounts. Here, we explore the requirements for technology tools that can support and encourage home practice, in a way that is appropriate and consistent with the core principles of mindfulness-based interventions. Interviews were held with a group of five highly experienced mindfulness teachers and a group of five participants who had previously completed an eight-week course. Data was subjected to thematic analysis. A key finding was that providing teachers with information on how students practice could support communication around difficulties with home practice. We also identified questions around the appropriateness of adapting the course in response to participant difficulties and participant preferences. Both teachers and students made numerous suggestions for ways to augment their training using technology, such as via practice reminders and provision of teacher-specific content. Finally, a major design issue for technology developers is how to support participants in reflecting on their experiences of mindfulness practice, and subsequent learning, but not to critically evaluate their practice.